In vitro synergistic activity of lidocaine and miconazole against Candida albicans - Maria da Conceição dos Santos Oliveira Cunha; Tarcísio Paulo de Almeida Filho; Francisco Afrânio Cunha; Ana Gesselena da Silva Farias; Ieda Pereira de Souza; Everardo Albuquerque Menezes (Acta Scientiarum. Health Sciences, 2017)
Candida albicans is the main yeast isolated from vulvovaginal candidiasis(VVC) and a major antifungal used to treat VVC is miconazole (MZ), it shows local toxic effects, such as irritation and burns. The lidocaine (LD) is a local anesthetic. The aim of this study was to evaluate the synergistic activity of LD/MZ against 19 strains of C. albicans isolated from vaginal secretion. 78.9% of the strains were susceptible to the combination LD/MZ, demonstrating synergism of drugs. These drugs can be used to produce vaginal creams to treat VVC, especially drug resistant.